Patient Management And Prevention Of Covid-19 Infection To Dental Practices During The Pandemic Literature Review - Ema Mayasari; Amelia Putri Nur Wulandari; Laili Wulandari (Universitas STRADA Indonesia, 2022)
At the end of 2019 until now, dentists have experienced difficulties in practice due to Corona Virus Disease or Covid-19. The outbreak was first identified in Wuhan city of Huabei province, China in December 2019 and was declared a pandemic by the WHO on March 11, 2020. The main impact of the fatal nature of this virus is a fairly high transmission ability from human to human through contact with droplets and aerosols. Covid-19 can infect the respiratory tract, causing mild pneumonia to death. Dental health workers are at high risk for exposure to Covid-19 infection due to the inability to maintain a distance between people of more than one meter and exposure to saliva, blood and other body fluids during dental procedures. In addition, many dental procedures can produce aerosols. The purpose of this study was to analyze patient management and Prevention of Covid-19 virus infection in dental clinics. This study is a literature review analyzed using PICOS by identifying scientific articles from 2016-2021 in English and Indonesian and full text. The databases used are PubMed, Research Gate, Google Scholar and Science Direct with a total of 627 articles identified using keywords dental patient management or Covid-19 prevention or PPE or clinical disinfection. The study results obtained 8 articles that discuss factors that affect patient management and Prevention of Covid-19 infection in dental clinics. Conclusion: initial screening of patients before arrival needs to be applied to categorize the solubility of the treatment to be given. Each patient should be considered infected with this virus in anticipation of treatment measures. Dental hygienists must use level 3 PPE and remove the PPE in order. Disinfect the room and tools that have been used to avoid droplets that stick to the surface.